1997
DOI: 10.1046/j.1365-3059.1997.d01-12.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of bean common mosaic necrosis virus in wild and forage legumes in Uganda

Abstract: Bean common mosaic necrosis virus (BCMNV) was isolated from Centrosema pubescens, Crotalaria incana, Lablab purpureus, Phaseolus lunatus, Senna bicapsularis, S. sophera, Vigna vexillata and an unidentified Crotalaria species growing in Uganda. Thirteen distinct isolates were characterized using symptoms, pathogenicity in differential bean cultivars, serology, immunosorbent electron microscopy, and seed and aphid transmission. Some isolates conformed with the characteristics of previously described strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 15 publications
2
20
0
2
Order By: Relevance
“…Both viruses are seedborne and transmitted by several aphid species in a non-persistent manner (Drijfhout, 1978). These viruses have been reported in common bean in many parts of the world including Europe (Drijfhout, 1978;Sáiz et al, 1995), U.S. (Kelly et al, 1983;Provvidenti et al, 1984), Canada (Tu, 1986), Mexico (Flores-Estévez et al, 2003) and Africa (Silbernagel et al, 1986;Spence & Walkey, 1995;Sengooba et al, 1997;Njau & Lyimo, 2000). BCMNV likely evolved more recently in the African continent (Spence & Walkey, 1995) and recombination has been observed between strains of BCMV and BCMNV (Silbernagel et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both viruses are seedborne and transmitted by several aphid species in a non-persistent manner (Drijfhout, 1978). These viruses have been reported in common bean in many parts of the world including Europe (Drijfhout, 1978;Sáiz et al, 1995), U.S. (Kelly et al, 1983;Provvidenti et al, 1984), Canada (Tu, 1986), Mexico (Flores-Estévez et al, 2003) and Africa (Silbernagel et al, 1986;Spence & Walkey, 1995;Sengooba et al, 1997;Njau & Lyimo, 2000). BCMNV likely evolved more recently in the African continent (Spence & Walkey, 1995) and recombination has been observed between strains of BCMV and BCMNV (Silbernagel et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…Among the methods available to prevent virus infection in common bean, genetic resistance is the most cost effective and durable (Drijfhout, 1978;Kelly et al, 1995;Miklas et al, 2000). In East Africa where BCMNV is found in wild legumes (Sengooba et al, 1997;Spence & Walkey, 1995), the only effective way to control these viruses is to plant resistant cultivars, otherwise susceptible bean plants can become infected from alternate hosts, growing adjacent to bean fields .…”
Section: Introductionmentioning
confidence: 99%
“…Njau and Lyimo (2000) showed that these viruses were systemic in four of the six infected plants. In Uganda, Sengooba et al (1997) (Spence and Walkey, 1995;Worrall et al, 2015).…”
Section: Alternative Hosts Of Bcmv and Bcmnvmentioning
confidence: 99%
“…The presence of BCMV in India was reported in 1963 by Yaraguntaiah and Nariani (1963) and Nagaich and Vashisht (1963). The virus, however, has not been studied systematically in India as compared to Latin America, Africa, Europe and USA (Morales and Bos, CMI/AAB Descriptions of Plant Viruses; Mckern et al 1992;Kelly 1997;Mavric and Vozlic 2004) where both BCMV and BCMNV have been reported to occur (Spence and Walkey 1995;Sengooba et al 1997;Silbernagel et al 2001). In India, most of the work on BCMV has been conducted in Himachal Pradesh, a North-western Himalayan state, where evaluations of over 100 virus isolates (unpublished data) have only revealed the presence of BCMV (Sharma et al 1999;Sharma 2000;Kapil et al 2005).…”
Section: Introductionmentioning
confidence: 99%